2000
DOI: 10.1029/1999jb900253
|View full text |Cite
|
Sign up to set email alerts
|

Record of seamount production and off‐axis evolution in the western North Atlantic Ocean, 25°25′–27°10′N

Abstract: Beyond the crest of the rift mountains (>4 Ma crust) faulting is no longer active, and changes in the off-axis seamount population reflect crustal aging processes as well as temporal changes in seamount production that occurred at the ridge axis. Estimates of population density for off-axis seamounts show a positive correlation to crustal thickness inferred from analysis of gravity data, suggesting that increased seamount production accompanies increased magma input at the ridge axis. We find no systematic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…Ridge show that our average density of 3.3 peaks of all sizes per 1000 km 2 is in the same order of magnitude as that obtained by Batiza et al (1989), but is an order of magnitude lower than that obtained by Smith & Cann (1990) and by Jaroslow et al (2000). The discrepancies observed in relation to the latter studies are probably due to the fact that they focused only on the immediate vicinity of the ridge, an area with exceptionally rugged topography (Smith & Cann 1990).…”
Section: Discussioncontrasting
confidence: 45%
“…Ridge show that our average density of 3.3 peaks of all sizes per 1000 km 2 is in the same order of magnitude as that obtained by Batiza et al (1989), but is an order of magnitude lower than that obtained by Smith & Cann (1990) and by Jaroslow et al (2000). The discrepancies observed in relation to the latter studies are probably due to the fact that they focused only on the immediate vicinity of the ridge, an area with exceptionally rugged topography (Smith & Cann 1990).…”
Section: Discussioncontrasting
confidence: 45%
“…They are large (-115 m average height, 1.5-2 km diameter), form a linear chain in the direction of plate spreading, and appear to survive intact following their formation on axis and subsequent uplift into the flanking crestal mountains and beyond (Figures lb and l c) [Rabain et al, 2001]. In contrast, typical MAR rift valley volcanoes are small (-60 m average height, <1 km diameter), isolated or piled on top of one another, and often destroyed or severely disrupted upon uplift from the inner valley [Smith and Cann, 1993;Bryan et al, 1994;Smith et al, 1999;Jaroslow et al, 2000]. Like many segments of the MAR [e.g., Brozena, 1986;Carbotte et al, 1991;Gente et al, 1992], the length of OH-1 has changed through time.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that many of these new seamounts undergo extensive tectonic deformation by normal faulting that reduces their original heights considerably ( Jaroslow et al, 2000). It is also evident that the increased sediment coverage on older seafloor (e.g., Ludwig and Houtz, 1979) is likely to bury the smallest and most numerous seamounts with height less than 100 m after a few tens of millions of years.…”
Section: Seamount Provincesmentioning
confidence: 99%